Women and gender in Islam: Historical roots of a modern debate - Ahmed, Leila (Yale University Press., 1992)
Explores the historical roots of the debate about women in Islamic societies by tracing the developments in Islamic discourses on women and gender up to the present. The book describes the gender systems in place in the Middle East both before and after the rise of Islam.
Keywords: 1800-1899; 1900-1999; approches et analyses; asie; cours; cycles supérieurs; discipline; fem1000; fem7000; femmes* musulmanes; féminisme islamique; genre; histoire; identités LGBTQIA2+; islam; lit3220; moyen-âge; orient; premier cycle; périodes historiques; rapports de domination; rapports sociaux de sexe; religion; ressource en ligne; régions géographiques; science des religions; sciences humaines; sexisme; sociologie; syrie; systèmes d'oppressions; thématiques; théologie; voiles islamiques

Rethinking masculinity: philosophical explorations in light of feminism - May, Larry; Strikwerda, Robert A.; Hopkins, Patrick D. (Rowman & Littlefield, 1992)
Are men naturally aggressive? What makes a good father? How can men form intimate friendships? In the new edition of this popular anthology, seventeen philosophers explore these and other questions that relate to what it means to be a man, including questions about pornography and homosexuality. New essays look at masculinity and violence, research on differences between men's and women's brains, impotence, sexual ambiguity, and whether black men have a moral duty to marry black women.
Section: xx, 236 pages
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; histoire et politique; masculinité; masculinités; patriarcat; philosophie; premier cycle; rapports sociaux de sexe; sciences humaines; soc2014; systèmes d'oppressions; thématiques